2021
DOI: 10.1080/19463138.2021.1958335
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Global to the Local: the challenges of multi-level governance for global policy implementation in Africa

Abstract: The New Urban Agenda (NUA) and Agenda 2030's Sustainable Development Goals (SDGs) recognise the key role of 'sub-national entities', including cities, in achieving sustainable development. However, since these global policy agendas were agreed and signed by national governments, implementing them at the local level requires a process of localisation to fit local realities. This paper analyses the national guidance (or lack of) and the resultant collaborations emerging between various levels of government in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Research shows that in developing countries, the management of the urbanization process according to the SDGs contributes to the global development agenda (Sietchiping & Omwamba, 2020). In their research, some authors indicate that in order for the SDGs implementation process to be effective, it is necessary to create a framework for multi‐stakeholder engagement and coordination at all levels of governance, especially between national authorities and cities (Croese et al, 2021). Harmonization and coordination of bottom‐up and top‐down mechanisms of governance require a metagovernance approach.…”
Section: Global Empowerment Of Subnational Authorities – Practical Qu...mentioning
confidence: 99%
“…Research shows that in developing countries, the management of the urbanization process according to the SDGs contributes to the global development agenda (Sietchiping & Omwamba, 2020). In their research, some authors indicate that in order for the SDGs implementation process to be effective, it is necessary to create a framework for multi‐stakeholder engagement and coordination at all levels of governance, especially between national authorities and cities (Croese et al, 2021). Harmonization and coordination of bottom‐up and top‐down mechanisms of governance require a metagovernance approach.…”
Section: Global Empowerment Of Subnational Authorities – Practical Qu...mentioning
confidence: 99%
“…In particular, cascaded structures through multi-level governance has been noted to enhance credible commitment and shift responsibility (Ciasullo et al, 2020). It is posited widely as a credible strategy to remedy political transaction costs and which seems pertinent in developing countries, where public sector decision-makers take advantage of political institutions that are often devoid of checks and control mechanism (Ciasullo et al, 2020;Croese, Oloko, Simon, & Valencia, 2021). Similarly, it has been observed that notwithstanding partner's important and enduring differences, the use of multilevel mechanisms for coordination enables partners involved in renegotiating common understandings in the partnership (Henderson & Smith-King, 2015;Le Ber & Branzei, 2010).…”
Section: Governing Through Structuresmentioning
confidence: 99%
“…Overall, there is a need for a governance system, where national, regional, and local decision-making centres collaborate (CIESIN). Therefore, multilevel governance is considered an overarching prerequisite in all urban governance processes (UN-Habitat; Croese et al, 2021), including climate change adaptation planning and implementation. Moreover, multilevel governance is required nowadays since most local governments or their departments seldom have the needed resources, power, and/or governance structure to carry out their responsibilities effectively and govern their constituencies in response to public policy challenges (UN-Habitat; Croese et al, 2021;van der Heijden, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Alexander Aylett's, 2015 adaptationfocused analysis of the UCGS highlights the different institutional structures utilised by different cities, different tactics for mainstreaming climate change into local government processes, and major challenges to local climate change action (Aylett, 2015). In the Global South, acting on climate change becomes more complex with pressing development needs, limited resources, and in many cases the lack of local autonomy (Croese et al, 2021). In addition, the variation in governance structures across the globe and especially within the Global South challenges the ability to replicate structures and solutions (Croese et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation